2013
DOI: 10.3389/fendo.2013.00111
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Circadian System, Cholesterol Synthesis, and Steroidogenesis Affects Various Aspects of Female Reproduction

Abstract: Circadian aspect of reproduction has gained much attention in recent years. In mammals, it is very important that the timing of greatest sexual motivation is in line with the highest fertility. Peripheral clocks have been found to reside also in reproductive organs, such as the uterus and ovary. The timing signal from the suprachiasmatic nucleus is suggested to be transmitted via hormonal and neural mechanisms, and could thus mediate circadian expression of target genes in these organs. In turn, estrogens from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 157 publications
(157 reference statements)
0
20
0
Order By: Relevance
“…It has been demonstrated that sex hormones may influence the expression of circadian genes (Nakamura et al 2001, Mostafaie et al 2009) and that circadian genes may play a role in hormone regulation (Urlep & Rozman 2013). Although, the exact mechanisms underlying this interplay are largely unknown, the differences we observed between post-and premenopausal women may be explained in part by differences in circulating levels of estrogen and progesterone in these two groups.…”
Section: Biological Mechanismsmentioning
confidence: 71%
“…It has been demonstrated that sex hormones may influence the expression of circadian genes (Nakamura et al 2001, Mostafaie et al 2009) and that circadian genes may play a role in hormone regulation (Urlep & Rozman 2013). Although, the exact mechanisms underlying this interplay are largely unknown, the differences we observed between post-and premenopausal women may be explained in part by differences in circulating levels of estrogen and progesterone in these two groups.…”
Section: Biological Mechanismsmentioning
confidence: 71%
“…It is accepted that a large variety of physiological functions, including reproductive processes, metabolism, and hormone secretions, depend on the circadian clock [Miller et al 2004;Urlep and Rozman 2013]. But circadian peripheral disruption increases disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…The key neuroendocrine cell populations involved in this event are those containing gonadotropin inhibiting hormone (GnIH), gonadotropic releasing hormone (GnRH) and kisspeptin (Kiss1). These neurosecretory cells receive monosynaptic projections from the SCN, but studies of these pathways have focused on females, with a dearth of evidence in males [27, 38] (Fig. 3).…”
Section: Sex Differences In Circadian Timing Systemmentioning
confidence: 99%
“…Neurons in the core SCN containing vasoactive intestinal peptide project directly to GnRH neurons in the medial preoptic area (MPOA), while those in the shell SCN containing vasopressin project to Kiss1 neurons in the anteroventral paraventricular nucleus (AVPV) [38]. Although the neuropeptidergic phenotype remains to be discovered, direct projection from the SCN to GnIH neurons in the dorsomedial hypothalamus (DMH) has been reported [39].…”
Section: Sex Differences In Circadian Timing Systemmentioning
confidence: 99%